2009
DOI: 10.1673/031.009.3101
|View full text |Cite
|
Sign up to set email alerts
|

Reared Microgastrine Wasps (Hymenoptera: Braconidae) from Yanayacu Biological Station and Environs (Napo Province, Ecuador): Diversity and Host Specialization

Abstract: The microgastrine braconid wasps recovered up through 2007 by the NSF-sponsored rearing project “Caterpillars and Parasitoids of the Eastern Andes in Ecuador” are summarized in terms of their host specialization and faunistic uniqueness. Two hundred fifty eight rearings of caterpillars resulted in records of Microgastrinae, distributed among 14 genera (Apanteles Förster, Choeras Mason, Cotesia Cameron, Diolcogaster Ashmead, Distatrix Mason, Dolichogenidea Viereck, Exix Mason, Glyptapanteles Ashmead, Hypomicrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 45 publications
1
24
0
1
Order By: Relevance
“…with these hosts (Yu et al, 2012) being this the first occurrence of this parasitoid on these Lepidoptera. Glyptapanteles species are solitary or gregarious parasitoids of macrolepidopterous larvae (Mason, 1981), with a cosmopolitan distribution, very common and diversified (Whitfield et al, 2009 There are several reports of the genus Pholetesor associated with Saturniidae (Wharton et al, 1997;Whitfield et al, 2009) in different areas and we have found this parasitoid on Saturniidae, Hemileucinae.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…with these hosts (Yu et al, 2012) being this the first occurrence of this parasitoid on these Lepidoptera. Glyptapanteles species are solitary or gregarious parasitoids of macrolepidopterous larvae (Mason, 1981), with a cosmopolitan distribution, very common and diversified (Whitfield et al, 2009 There are several reports of the genus Pholetesor associated with Saturniidae (Wharton et al, 1997;Whitfield et al, 2009) in different areas and we have found this parasitoid on Saturniidae, Hemileucinae.…”
Section: Discussionsupporting
confidence: 51%
“…The Microgastrinae were the most abundant in the two environments, however, presenting the largest number of genera in the agrosilvopastoral system; this subfamily is cosmopolitan, highly diversified, comprising koinobiont endoparasitoids, solitary or gregarious on larvae of Lepidoptera (Mason, 1981;Whitfield et al, 2009). The other subfamilies of Braconidae occurred to a lesser extent, and included a variety of genera, mainly endoparasitoids of Lepidoptera larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The species are mostly gregarious in nature with only a few solitary forms. They mainly parasitize caterpillars of Noctuidae, Geometridae and Saturniidae (Whitfield et al 2009). Literature review shows that nearly 34 species are recorded from the Indian region (unpublished data of the first author) with a few cosmopolitan species.…”
Section: Issnmentioning
confidence: 99%
“…Both genera are easily confused (Mason 1981;Whitfi eld et al 2009), and the correct generic assignment of some of the species is often limited by subtle and subjective characters. A comprehensive study of those genera (plus a few others, see for example, van Achterberg 2002b) is badly needed to redefi ne its limits with accuracy.…”
Section: Genus Dolichogenidea Viereck 1911mentioning
confidence: 99%